2017
DOI: 10.6002/ect.tond16.l16
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Hepatocellular carcinoma is the most common primary liver malignancy. Liver transplantation has been a successful therapy for selected patients with hepatocellular carcinoma. Since 1996, Milan criteria have been universally recognized as the guidelines for selecting patients with hepatocellular carcinoma for orthotopic liver transplantation. However, the simple use of tumor size and number has been insufficient to indicate the biologic features of hepatocellular carcinoma and to predict the risk of tumor recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
0
10
0
2
Order By: Relevance
“…Manini et al[ 28 ] showed the efficacy of DEB-TACE for treatment of BCLC A stage HCC patients prior to liver transplantation based on the Milan criteria[ 29 ]. The median diameter of the target tumors was 24 mm, similar to that in our study, and achieving CR with initial DEB-TACE was found to be an important prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Manini et al[ 28 ] showed the efficacy of DEB-TACE for treatment of BCLC A stage HCC patients prior to liver transplantation based on the Milan criteria[ 29 ]. The median diameter of the target tumors was 24 mm, similar to that in our study, and achieving CR with initial DEB-TACE was found to be an important prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical ablation is the most effective method for localized HCC with Child-Pugh A or B and a single tumor diameter <5 cm [ 29 ]. Liver transplantation is considered to be an effective method for the treatment of patients with end-stage liver disease or primary liver cancer, but preventing the recurrence of HCC after transplantation and improving the survival rate of patients remains a challenge [ 30 ]. In recent years, small molecule drugs targeting epidermal growth factor receptor, vascular endothelial growth factor and multiple amino acid kinase have been gradually applied to the clinical treatment of patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…These criteria take in account the morphological parameters such as size and number of nodules (one lesion smaller than 5 cm or, alternatively, up to three lesions, each smaller than 3 cm), with diagnostic imaging techniques like contrast CT and MRI that act as main tools used to reach diagnosis and prognostic evaluation of HCC [ 6 ]. Nonetheless, more recently, MC have been criticized because they appear over conservative, thus refraining a significant number of patients from a possible curative treatment [ 7 ]. In this sense, nowadays, it is generally accepted that MC cutoffs have to be extended in order to increase the number of HCC patients eligible for LT [ 8 ].…”
Section: Introductionmentioning
confidence: 99%